Extension of Cauchy Riemann System in Higher Dimensions - Dang Van Khai (Bach Khoa, 2020)
Chapter 1: Holomorphic Vector in m - dimensional Euclidean Space ; Chapter 2: Holomorphic Functions Taking Values in Clifford Algebras ; Chapter 3: A class of First order Elliptic system.